1987
DOI: 10.1161/01.res.61.6.797
|View full text |Cite
|
Sign up to set email alerts
|

Metaiodobenzylguanidine [131I] scintigraphy detects impaired myocardial sympathetic neuronal transport function of canine mechanical-overload heart failure.

Abstract: In heart failure secondary to chronic mechanical overload, cardiac sympathetic neurons demonstrate depressed catecholamine synthetic and transport function. To assess the potential of sympathetic neuronal imaging for detection of depressed transport function, serial scintigrams were acquired after the intravenous administration of metaiodobenzylguanidine [131I] to 13 normal dogs, 3 autotransplanted (denervated) dogs, 5 dogs with left ventricular failure, and 5 dogs with compensated left ventricular hypertrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…MIBG studies had shown both sympathetic denervation and reinnervation in injured myocardium in both ischemic and nonischemic cardiomyopathy in humans. 37,38 A consequence of peripheral nerve injury resulting in Wallerian degeneration is regeneration via nerve sprouting. The axonal regeneration is slow but accelerates to reach a constant rate by third day after injury and is triggered by NGF produced by surrounding myocardium.…”
Section: Myocardial Infarction Heart Failure and Sympathetic Innervmentioning
confidence: 99%
“…MIBG studies had shown both sympathetic denervation and reinnervation in injured myocardium in both ischemic and nonischemic cardiomyopathy in humans. 37,38 A consequence of peripheral nerve injury resulting in Wallerian degeneration is regeneration via nerve sprouting. The axonal regeneration is slow but accelerates to reach a constant rate by third day after injury and is triggered by NGF produced by surrounding myocardium.…”
Section: Myocardial Infarction Heart Failure and Sympathetic Innervmentioning
confidence: 99%
“…The norepinephrine storage mechanism lags behind the specific membrane mechanism for uptake in the reinnervated heart after surgical denervation. [34][35][36] It is important to caution that such MIBG defects may have also arisen from some physiological change in the uptake pathway for MIBG such as might occur if there were competition for the uptake mechanism from a sympathetic agent such as norepinephrine. Nevertheless, it appears that a similar interplay between myocardial injury and autonomic nervous system innervation may exist in humans.…”
Section: New Observationsmentioning
confidence: 99%
“…24,25) A decrease in myocardial MIBG accumulation and NE has been reported in heart failure 21,[26][27][28][29] and also in experimental models of MI. 19,30) In the present study, it is unlikely that reduced MIBG accumulation and NE content would be due to sympathetic denervation by the surgical procedure because MIBG accumulation and NE content did not decrease in the sham-operated rats.…”
Section: Discussionmentioning
confidence: 92%